Pemetaan Daerah Potensi Rawan Banjir Menggunakan Metode Overlay - Muhammad Seprianto; Mustamin Anggo; Surdin; La Harudu; Septianto Aldiansyah (Jurnal Penelitian Pendidikan Geografi, 2024)
Andoolo District is an area that is very prone to flooding, such as the flash flood in 2013. The purpose of this study was to determine the areas prone to flooding and to determine the data accuracy on the map based on the actual situation in Andoolo District. This type of research is survey and mapping research. Primary data was collected by direct review of the flood location and documentation. Secondary data includes administrative maps, soil type maps, rainfall maps, land use maps, slope maps, and distance from river maps collected from related agencies. Flood vulnerability maps are grouped into classes of not vulnerable, rather vulnerable, quite vulnerable, vulnerable, and very vulnerable. The vulnerable level occupies the largest proportion of 5,128.54 ha or 52% of the total area. The accuracy of the data on the map and the actual situation shows that there are 5 villages exposed to flooding, namely Alangga, Andoolo, Punggapu, Lalobao, and Potoro. s